How hours allocated to year-round auditing procedures affect audit quality - Kim, Sangil; Kang, Minjung; Lee, Ho Young; Mande, Vivek (Managerial Auditing Journal, 2024)
Purpose: This paper aims to examine how the allocation of audit hours to the year-round procedures, based on the risk of material misstatements in financial statements, impacts audit quality. Design/methodology/approach: Using a data set on audit hours spent on year-round and year-end procedures, the authors build an empirical model for testing the effectiveness of year-round auditing of Korean public firms during the period of 2014–2018. Findings: The initial tests do not show that proportionate increases in year-round procedures increase audit quality. However, after the authors control for the risk of material misstatements, the authors find that proportionate increases in year-round audit hours generally increase audit quality, except for high-risk firms where audit quality increases only as year-end hours proportionately increase. For high-risk firms, the results suggest that increases in year-round audit procedures occur at the cost of the essential year-end work. Similarly, except for high-risk firms, the authors find that the allocation of more audit effort to year-round procedures improves audit efficiency. Originality/value: To the best of the authors’ knowledge, this study provides some of the first empirical evidence showing how a risk-based approach to allocating audit effort over the duration of an audit can impact audit quality and efficiency. Regulatory bodies, such as the International Auditing and Assurance Standards Board and Public Company Accounting Oversight Board, which consider the proper allocation of audit hours as a key audit quality indicator, should find the results useful.
Keywords: Audit hours; Audit quality; Risk of material misstatement; Year-end audit; Year-round audit